2011
DOI: 10.1002/jor.21512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cementing technique and cement type on thermal necrosis in hip resurfacing arthroplasty—a numerical study

Abstract: Femoral fractures within resurfacing implants have been associated with bone necrosis, possibly resulting from heat generated by cement polymerization. The amount of heat generated depends on cement mantle volume and type of cement. Using finite element analysis, the effect of cement type and volume on thermal necrosis was analyzed. Based on CT-data of earlier implantations, two different models were created: a thick mantle model, representing a low-viscosity ''cement filling'' technique, and a thin mantle mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…With increased thickness of the cement mantle at the proximal humerus adjacent to the tuberosities, temperatures may reach levels high enough to produce thermal bone necrosis. 17,23 The exothermic effects of polymethyl methacrylate were recently studied in a cadaver model that compared the cortical bone temperatures of a full cementation technique with an impaction grafting technique similar to the black and tan technique used in this study. 31 The temperature observed at the surgical neck adjacent to the location of the tuberosity decreased 23% in the impaction grafting technique, dropping the maximum recorded temperature from 52.4 AE 8.1 C to 40.4 AE 4.8 C, below the 47 C threshold thought to create thermal bone necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…With increased thickness of the cement mantle at the proximal humerus adjacent to the tuberosities, temperatures may reach levels high enough to produce thermal bone necrosis. 17,23 The exothermic effects of polymethyl methacrylate were recently studied in a cadaver model that compared the cortical bone temperatures of a full cementation technique with an impaction grafting technique similar to the black and tan technique used in this study. 31 The temperature observed at the surgical neck adjacent to the location of the tuberosity decreased 23% in the impaction grafting technique, dropping the maximum recorded temperature from 52.4 AE 8.1 C to 40.4 AE 4.8 C, below the 47 C threshold thought to create thermal bone necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a concern that this technique might have long-term detrimental effects related to stress shielding [24,29] or thermal necrosis associated with the increase in overall cement needed for component fixation [15,18,20]. Our study compared survivorship, hip scores, and other radiographic findings between hips resurfaced with a cemented metaphyseal stem and hips resurfaced with a press-fit metaphyseal stem.…”
Section: Discussionmentioning
confidence: 99%
“…All currently available hip resurfacing prostheses feature a metaphyseal stem, typically left uncemented, which helps to facilitate proper alignment for insertion of the femoral component. Cementing this metaphyseal stem increases the area for fixation between the bone and the prosthesis, but this increases the total amount of bone cement needed for fixation, and several studies suggest that the heat generated from the cementing process could lead to thermal necrosis of the surrounding cancellous bone [15,18,20], which could in turn cause femoral neck fracture or femoral loosening. Additionally, cementing the stem may alter the load transfer between the femoral component and the femoral neck, leading to adverse modifications of the proximal femur [24,29].…”
Section: Introductionmentioning
confidence: 99%
“…The modeling method of prescribed temperature decrease used in the current study is limited because the actual maximal temperature varies depending on thermal boundary conditions such as cement and stem initial temperature and total volume of cement (Little et al, 2008;Madrala and Nuño, 2010;. Recent experimental studies showed maximal temperatures of 80 1C (Madrala and Nuño, 2010) to 110 1C (Janssen et al, 2012;Race et al, 2007) for bone cement during curing: the current study's hypothesis of a 80 1C maxima is therefore not an extreme value.…”
Section: Discussionmentioning
confidence: 77%